The emotional experiences of Paralympic swimming medalists: not all wins and losses are equal - Martin, J. (Adapted Physical Activity Quarterly, 2023)
The goal of this study was to determine if emotional expressions at the end of swimmers` 2016 Paralympic races varied according to medal won and if their race wins and losses were close or not close. Using FaceReader software, videos of 46 races of medal-winning Paralympic (M age = 24.6; SD = 5.4) swimmers` faces (78 males and 60 females) from 22 countries were analyzed. Silver medalists were angrier and sadder than gold medalists and angrier and more disgusted than bronze medalists. Swimmers who swam slower than their 2015 best time were angrier than Paralympians who swam faster. Paralympians who finished lower than their 2015 world ranking had more neutral emotions and were less happy than Paralympians who finished higher. Gold medalists who narrowly defeated silver medalists were less happy and more fearful than gold medalists who won easily. Bronze medalists with close wins had fewer neutral emotions and were happier, less angry, and more surprised than bronze medalists with not-close wins. All medalists with close wins were more surprised than medalists with easier wins. Bronze medalists with close losses to silver medalists were happier and less angry than bronze medalists who lost more easily. Effect sizes ranged from d = 0.27 to 1.01. These results provide theoretical support to basic emotion theory and confirm the anecdotal observations that Paralympic competition generates wide-ranging and diverse emotions.